Pathologies connected with the work of IT specialist in the organizational system of the company = Patologie związane z pracą informatyka w systemie organizacyjnym firmy - Haber, Lesław H.; Garwol, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
In the article are described the dangers to which the IT specialists, working for many hours with the usage of computer, Internet, and the cellular phone in the organizations of different type, are exposed to. At the beginning there was described the influence of digitalization to the changes in the system of organization management. In the further part one can find the trial of the answer to the question what is the place and the role of the IT specialists in the organizations. Then there are presented the results of the research carried out by the authors concerning the sources of dangers connected with the long work of IT specialists in the organization with the usage of achievements of the modern information technology.
Keywords: informatyk; technologia teleinformatyczna; internet; uzależnienie; organizacja; praca; IT specialist; information technology; addiction; work; organization